2013
DOI: 10.1159/000346153
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement with and without Coronary Artery Bypass Graft Surgery in Octogenarians: Is It Safe and Feasible?

Abstract: Introduction: Octogenarians are often denied complex surgical intervention. We evaluated the rationality of this bias by comparing the outcomes of octogenarians undergoing aortic valve replacement (AVR) with or without coronary artery bypass grafting (CABG), to those of younger patients. Methods: Data on 476 patients (≥80 years) who underwent AVR or AVR/CABG were compared to the Society of Thoracic Surgeons (STS) database. Results: One hundred and seventeen octogenarians underwent AVR and 263 underwent AVR/CAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…This is also in keeping with more recent data attesting to the safety of coronary revascularization at AVR even in high-risk elderly patients. 18,19 Our findings also clearly demonstrate superior 5-and 8-year survival rates in patients with CABG versus medical management for coexistent CAD at index AVR. After adjusting for the confounding effects of older age, female sex, peripheral vascular disease, reduced ejection fraction, diabetes mellitus, and NYHA class III to IV, CABG was independently associated with a more than one-third reduction in the risk of late all-cause mortality.…”
Section: Discussionsupporting
confidence: 59%
“…This is also in keeping with more recent data attesting to the safety of coronary revascularization at AVR even in high-risk elderly patients. 18,19 Our findings also clearly demonstrate superior 5-and 8-year survival rates in patients with CABG versus medical management for coexistent CAD at index AVR. After adjusting for the confounding effects of older age, female sex, peripheral vascular disease, reduced ejection fraction, diabetes mellitus, and NYHA class III to IV, CABG was independently associated with a more than one-third reduction in the risk of late all-cause mortality.…”
Section: Discussionsupporting
confidence: 59%
“…Abel ve ark. miyokardiyal revaskülarizasyon geçiren ileri yaşlı hastalardaki mortalitenin genç hastalarda görülenden 2 kat daha fazla olduğunu bildirmiştir (9). Güncel çalışmalarda mortalitenin özellikle 80 yaş ve üzeri olan hastalarda yüksek olduğunu ortaya koymuştur (10).…”
Section: Discussionunclassified
“…However, advanced age was not an independent risk predictor of early mortality. Both Abel et al 12) and Thourani et al 7) reported similar results.…”
Section: Early Mortalitymentioning
confidence: 55%